Interatrial block is related to atrial dysfunction in hypertensive subjects. (8th February 2021) - Tirapu Sola, L; Loncaric, F; Mimbrero, M; Mendieta, LG; Nunno, L; Sanchis, L; Doltra, A; Montserrat, S; Bijnens, B; Sitges, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): La Marató TV3 Background: Interatrial block (IAB), a delay of conduction of the sinus stimulus from right to left atria (LA), is defined as surface ECG P-wave duration ≥120 ms. Arterial hypertension (AH) and IAB have been related to development of atrial fibrillation. Aim: To investigate the IAB prevalence in a cohort of AH patients and relate it to LA function. Methods: 162 patients with well-regulated AT were included. 12-lead ECG were performed and analysed with a digital caliper. 2D and 3D echocardiography were performed, and LA function assessed with speckle-tracking deformation imaging.  Results: The median age was 56 ± 6 years, 54% were males. Average duration of AH was 10 ± 6 years. IAB was seen in 25% of AH patients.  The comparison between groups is shown in Table 1. There were no differences in demographic characteristics,   QRS complex duration (p = 0.179) or left ventricular (LV) size and function between subgroups. LA was enlarged in IAB patients, which was coupled with impairment of the LA reservoir strain.  Conclusion: Our results show considerable prevalence of IAB in AH patients. The demonstrated LA enlargement and function impairment is not associated with LV dysfunction, therefore suggesting an independent role of IAB in atrial remodeling.